Design of 1.8V supply subthreshold voltage reference - Wang, Xiaoying (2016)
Voltage reference circuit plays a critical role in most of the electronic devices with high precision requirements. The relatively constant output voltage is irrespective of supply variations, temperature change, passage of time and so on. Conventionally, an op-amp based voltage reference requires both MOSFET and BJT to realize the compensation in temperature dependent factors. Nonetheless, the process used in this design is Austria Micro System 0.18μm CMOS with 1.8V supply. Hence the headroom of device operation is limited due to low supply voltage. Instead of making use of the BJT currents’ temperature characteristics, MOSFET’s subthreshold region of operation was employed to generate temperature dependent currents. In this project, a 1.8V supply voltage reference circuit was constructed. Simulations and analyses were performed in Cadence Virtuoso Analog Design Environment. The outcome of this voltage reference achieves 1V output voltage with temperature coefficient of 58.9ppm/°C and power supply rejection ratio of 42.37dB.